Respon struktur akibat perubahan jarak stiffener pada car deck Kapal Ferry Ro-Ro - Alamsyah Alamsyah; Septiany Tri Pangestu; Amalia Ika Wulandari (Universitas Muhammadiyah Metro, 2021)
Ro-Ro type trans ships have a Car Deck which is useful for accommodating cargo in the form of vehicles. The construction of the deck must be strong enough so that it does not suffer structural damage when working with a certain load. In this case the stress strain becomes very important as an element of deck strength. As for what affects the strength of the deck construction, one of which is the stiffener distance. This purpose of research to determine the response of the car deck structure with variations in stiffener distance to the stress-strain value. The method used is the Finite Element Method. The results of detected the maximum stress value at a stiffener distance of 550 mm 325.471 N/mm2 with a maximum strain of 3.33 x 10-2 mm, for a stiffener distance of 650 mm the maximum stress was 407.521 N/mm2 and a maximum strain of 3.35 x 10-2 mm, a stiffener distance of 750 mm the maximum stress generated is 444.129 N/mm2 with a maximum strain of 3.36 x 10-3 mm, a stiffener distance of 850 mm, the maximum stress generated is 448.469 N/mm2 with a maximum strain of 3.43 x 10-3 mm. For a stiffener distance of 950 mm, the maximum stress is 452.567 N/mm2 with a maximum strain of 3.53 x 10-3 mm.